Microstructure and hardness investigation of different welding passes in weld zones: Untersuchung der Mikrostruktur und Härte in Schweißzonen für verschiedene Schweißlagen. Issue 4 (May 2015) - Awang, M.; Raza, S. K.; Yahaya, M. S. A.
Abstract : Friction stir welding is a solid state joining process that uses frictional heat generated from non‐consumable rotating tool to weld two metals together. This present work aims at the investigation of the effect of multiple pass welding on microstructure and hardness in weld zones. Aluminium alloy 6061‐T6 sheets with a dimension of 100 mm × 100 mm × 10 mm are butt‐welded in three different passes; single pass, double pass on the same side and double pass on different sides. The microstructure of the welded samples and its hardness are analysed and the effect of passes are investigated. Visual inspection on the weld joint shows that double passes experienced smaller wormhole defect as compared to single pass. Microstructure investigation shows slight difference in the grain size among all passes. The quantity of precipitates is highest at the thermo‐mechanically affected zone (TMAZ) compared with other regions. The double passes on same the side exhibits the highest hardness value with 61.1 HV in the stir zone compared with other welding passes studied. However, all regions show lower hardness values as compared to the parent material in all combinations of passes.